A new magnesium bisulfite pretreatment (MBSP) development for bio-ethanol production from corn stover. (January 2016) - Yu, Heng; Ren, Jiwei; Liu, Lei; Zheng, Zhaojuan; Zhu, Junjun; Yong, Qiang; Ouyang, Jia
Abstract: This study established a new more neutral magnesium bisulfate pretreatment (MBSP) using magnesium bisulfate as sulfonating agent for improving the enzymatic hydrolysis efficiency of corn stover. Using the MBSP with 5.21% magnesium bisulfate, 170 °C and pH 5.2 for 60 min, about 90% of lignin and 80% of hemicellulose were removed from biomass and more than 90% cellulose conversion of substrate was achieved after 48 h hydrolysis. About 6.19 kg raw corn stover could produce 1 kg ethanol by Saccharomyces cerevisiae . Meanwhile, MBSP also could protect sugars from excessive degradation, prevent fermentation inhibition formation and directly convert the hemicelluloses into xylooligosaccharides as higher-value products. These results suggested that the MBSP method offers an alternative approach to the efficient conversion of nonwoody lignocellulosic biomass to ethanol and had broad space for development.